a)
2x-3y=5
x+y=10 inmultim cu 3
3x+3y=30
se aduna
2x-3y=5
3x+3y=30
5x=35
x=7
y=10-7=3
b)
x-y=-1 inmultim cu 2
3x+2y=7
2x-2y=-2
5x=5
x=1
y=2
c)40x+3y=15
10x-11y=9 inmultim cu -4
40x+3y=15
-40x+44y=-36
47y=-21
y=-21/47
x=(9+11y)/10=[9+11(-21/47)]/10=(423-231)/470=192/470=96/235
d) x+y=5 inmultim cu 6
3x-6y=9
6x+6y=30
3x-6y=9
9x=39
x=39/9
y=5-x=5-39/9=(45-39)/9=6/9=2/3
e) 2x-4y=-6
3x-2y=-7 inmultim cu -2
-6x+4y=14
2x-4y=-6
-4x=8
x=-2
y=(3×(-2)+7)/2=(-6+7)/2=1/2
f) 5x-2y=1 inmultim cu -3
15x-3y=-3
-15x+6y=-3
9y=-6
y=-2/3
x=[1+2(-2/3)]/5=(1-4/3)/5= -1/15
g) 12x-7y=2 inmultim cu -5
15x-5y=-5 inmultim cu 7
-60x+35y=-10
105x-35y=-35
45x=-45
x=-1
y=[-2+12×(-1)]/7=(-2-12)/7=-2
h) 2x+3y=5 inmultim cu -2
5x+2y=-2 inmultim cu 3
-4x-6y=-10
15x+6y=-6
11x=-16
x=16/11
y= (5-2×16/11)/3= (55-32)/11×3=23/33